FAKTOR YANG BERHUBUNGAN DENGAN KECELAKAAN KERJA PADA PETUGAS PEMADAM KEBAKARAN DI KOTA PEKANBARU - Muawwanah, Sholihatun; Syukaisih, Syukaisih; Muhamadiah, Muhamadiah; Devis, Yesica; Suherman, Suherman (Ensiklopedia of Journal, 2025)
Occupational accidents experienced by firefighters can have serious impacts on their safety. Therefore, understanding the factors that influence the risk of occupational accidents is crucial. This study aims to identify the factors associated with occupational accidents among firefighters in Pekanbaru City in 2025.This research uses a quantitative method with a cross-sectional design. A total of 163 respondents were selected from a population of 277 firefighters using a proportional random sampling technique. The independent variables in this study include supervision, behavior, the implementation of Standard Operating Procedures (SOP), and the availability of Personal Protective Equipment (PPE). Data were collected through questionnaires and analyzed using the Chi-Square test. The results show a significant relationship between supervision and the incidence of occupational accidents (p-value = 0.0010, POR = 2.661), as well as the availability of PPE (p-value = 0.000, POR = 5.516). Meanwhile, no significant relationship was found between behavior and SOP implementation with the incidence of occupational accidents. Effective supervision and the adequate availability of PPE play a vital role in reducing the risk of occupational accidents among firefighters.The findings of this study are expected to serve as a basis for the Fire Department of Pekanbaru City in developing programs to improve occupational safety and to provide recommendations regarding training and the optimal provision of protective equipment. Keywords: Supervision, Behavior, SOP, Availability of PPE, Firefighters